Low Levels of High-Density Lipoprotein Cholesterol Are Linked to Impaired Clopidogrel-Mediated Platelet Inhibition. (October 2018) - Wadowski, Patricia P.; Lee, Silvia; Kopp, Christoph W.; Koppensteiner, Renate; Panzer, Simon; Gremmel, Thomas
Low high-density lipoprotein cholesterol (HDL-C) levels are an independent predictor of ischemic events in patients with atherosclerotic cardiovascular disease. This may in part be due to decreased clopidogrel-mediated platelet inhibition in patients with low HDL-C. We investigated the association of HDL-C with on-treatment platelet reactivity to adenosine diphosphate (ADP) in 314 patients on dual antiplatelet therapy with clopidogrel and aspirin undergoing angioplasty and stenting. Platelet P-selectin expression was assessed by flow cytometry, and platelet aggregation was determined by the VerifyNow P2Y12 assay and the Impact-R. High-density lipoprotein cholesterol levels were inversely associated with P-selectin expression and the VerifyNow P2Y12 assay (both P ≤ .01). Moreover, we found a positive correlation of HDL-C with surface coverage by the Impact-R ( P = .003). Patients with low HDL-C (≤35 mg/dL) exhibited a significantly higher P-selectin expression in response to ADP and higher platelet aggregation by the VerifyNow P2Y12 assay and the Impact-R than patients with normal HDL-C (>35 mg/dL; all P < .05). High on-treatment residual platelet reactivity by the VerifyNow P2Y12 assay occurred significantly more frequently in patients with low HDL-C levels than in those with normal HDL-C (47.4% vs 30.1%, P = .01). In conclusion, low HDL-C is linked to impaired clopidogrel-mediated platelet inhibition after angioplasty and stenting.